2018
DOI: 10.1002/suco.201800097
|View full text |Cite
|
Sign up to set email alerts
|

Simplified elastic design method using equivalent span ratio for two‐way concrete composite slabs with precast ribbed panels

Abstract: This paper analyzes the existing problems in the practical engineering design, resulting from the mechanical properties of two-way composite concrete slabs with precast ribbed panels (CSPRPs). Due to the influence of the structurally orthotropic characteristic, the calculation formulas for the deflection and bending moments of a CSPRP with three supported edges and one clamped edge under a uniformly distributed load are solved using the load superposition method and the orthotropic plate theory. The CSPRP is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Han et al [11] explored the bending resistance of pre-stressed composite plates, revealing that the cracking load and stiffness depend significantly on the reinforcement ratio and pre-stress levels. Concurrently, Huang et al [12] analyzed the elasticity of bidirectional concrete composite plates, proposing a method to simplify anisotropic plates into isotropic ones. Wang [13,14] studied the longitudinal shear strength and capacity of steel-concrete composite beams with novel joint designs, observing that combining short transverse reinforcements with rectangular slots offers an efficient and effective solution for composite action compared to different precast elements.…”
Section: Introductionmentioning
confidence: 99%
“…Han et al [11] explored the bending resistance of pre-stressed composite plates, revealing that the cracking load and stiffness depend significantly on the reinforcement ratio and pre-stress levels. Concurrently, Huang et al [12] analyzed the elasticity of bidirectional concrete composite plates, proposing a method to simplify anisotropic plates into isotropic ones. Wang [13,14] studied the longitudinal shear strength and capacity of steel-concrete composite beams with novel joint designs, observing that combining short transverse reinforcements with rectangular slots offers an efficient and effective solution for composite action compared to different precast elements.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed calculation formulas could predict the cracking and ultimate moment with good accuracy. Furthermore, the simplified design method of two‐way CSPRPs was introduced by Huang et al 9 based on its mechanical behavior. Yardim et al 10 conducted experimental investigations on a ferrocement‐AAC composite slab which had the advantage of lightweight.…”
Section: Introductionmentioning
confidence: 99%
“…The shear keys can also be connected to temporary I-beams to increase the stiffness of the PBSs to realise support-free construction (Figure 2b). There are large bodies of systematic research on each [3][4][5][6][7][8][9][10][11]. Liu et al [12] confirmed the practicality of using STLSs by empirical testing; Ma et al [13] investigated its mechanical properties in construction and in service by testing and numerical modelling; Zhao et al [14] analysed the influence of parameters, such as concrete strength and truss height and diameter, on the mechanical properties of STLSs using ANSYS software; and Cheng [15] developed a short-term stiffness model for STLSs from theoretical analysis.…”
Section: Introductionmentioning
confidence: 99%